Double effort test for evaluation of aerobic capacity of diet-induced obese rats - Brandão, Bruna Brasil [UNESP]; de Souza, Lidiane Moreira [UNESP]; Trombetta, Beatriz de Novais Oliveira [UNESP]; Pastre, Carlos Marcelo [UNESP]; Papoti, Marcelo; Seraphim, Patricia Monteiro [UNESP] (FapUNIFESP (SciELO), 2013)
Introduction: The literature lacks studies about lactate actions and some limitations in studies involving healthy individuals or patients with some metabolic disorder. Objectives: This study aimed to evaluate the protocol of double effort test for obese-induced rats. Methods: Fourteen male Wistar rats were divided into two groups: Control (Con) and Obese (Obe). The control group was fed with standard chow and water ad libitum. The obese group was fed with standard chow, water ad libitum and hyperlipidic diet. Twelve weeks after the beginning of the hyperlipidic diet, insulin tolerance test, Maximal Lactate Steady State (MLSS) test and the double efforts test were performed. Results: The diet was effective to promote obesity. The obese group decreased insulin sensitivity in approximately 19% (Con = 2.156 ± 0.1187 AU vs Obe = 1.742 ± 0.1551 AU). The lactate concentration and velocity of anaerobic threshold at MLSS test were 3.780 ± 0.09 mmol/L e 18 m.min-1 in both groups. The velocity of anaerobic threshold estimated by double efforts test was 15.59±0.653 m.min-1 in Con group control animals and 16.42±0.672 m.min-1 in Obe group. The double effort test underestimated around 13% and 8.7% the aerobic capacity in control and obese groups respectively, however, presented significant correlation with MLSS (r = 0,88; P < 0,0075 controls / r = 0,92; P < 0,0031 obese). Conclusion: So, the double effort test can be an interesting alternative to evaluate the aerobic capacity for both healthy sedentary and obese animals.
Keywords: Lactic acid; Obesity; Running